Regulatory Harmonization of Plea Bargaining for Petty Corruption in Indonesia’s Criminal Justice System - Eben Patar Opsunggu; Azis Budianto (Yayasan Cendekia Gagayunan Indonesia, 2025)
The eradication of corruption in Indonesia continues to face structural challenges, particularly in the handling of petty corruption cases that involve relatively small state losses but consume disproportionate law enforcement resources. This study aims to analyze the urgency, feasibility, and regulatory implications of implementing a plea bargaining mechanism as an alternative resolution model for petty corruption cases within Indonesia’s criminal justice system. Using a normative juridical method with statutory and conceptual approaches, this research examines relevant laws, including the Anti-Corruption Law, the Criminal Procedure Code (KUHAP), and the Prosecutor’s Office Law, as well as comparative practices from the United States, Italy, and the Philippines. The findings indicate that the absence of explicit legal regulation has resulted in procedural rigidity, inefficiency, and suboptimal recovery of state losses in minor corruption cases. Plea bargaining, if strictly limited and transparently regulated, has the potential to enhance legal efficiency, prioritize restitution of state losses, reduce judicial and correctional burdens, and support a more restorative justice orientation. This study concludes that regulatory harmonization through limited revisions to the Corruption Law and KUHAP, complemented by clear prosecutorial guidelines issued by the Attorney General’s Office, is essential to ensure accountability, legal certainty, and public trust. Properly designed plea bargaining should be positioned not as a form of impunity, but as a strategic instrument to optimize corruption eradication while upholding substantive justice and the rule of law.